Relationship Between Depressive Symptoms With Vitamin D Level Among Nursing Students In Selected Colleges At Mangaluru - Sukesh, Shreya Chakraborty, Dr. Nalini M (Drugs and Cell Therapies in Hematology, 2021)
Background The human body must have Vitamin D to absorb calcium and promote bone growth. A level of 30ng/ml to 50ng/ml is considered an adequate level of Vitamin D. Vitamin D deficiency exists when the concentration of 25(OH) D in the blood serum is 30 ng/ml, or less[12]. Many studies revealed that most of the nurses are Vitamin D deficient, and the rate of depression is quite high among them[6]. Aim The present study endeavours to find the relationship between depressive symptoms with the Vitamin D level. Methodology Quantitative research approach with a cross-sectional survey research design was adopted in the study. Total of 138 nursing students was included in the study to assess the depressive symptoms. Among them 44 students those who had fallen under borderline clinical depression to extreme depression according to Beck Depression Inventory were taken to assess the Vitamin D level. The Vitamin D level was assessed by Lab investigation (Vitamin D blood serum test 25(OH)D).Collected data was summarised using Descriptive and inferential statistics. Results In this study the researcher has found a negative relationship between depressive symptoms and the Vitamin D level(‘p’ value is <0.05 and the Pearson relation value is -0.347). In other words, as Vitamin D decreases depressive symptoms increases. Also, educational status(p= 0.001) and place of residence(p=0.018) were found to be significantly associated with depressive symptoms(p<0.05). Conclusion In this present study, the researcher has found that majority of nursing students are having dpreessive symptoms and Vitamin D deficiency, which needs immediate attension. Also present study finding revealed negative relationship between Vitamin D and depression, but it require further extensive research.